Virtual Reality Design and Realization of Interactive Garden Landscape. (18th June 2021) - Zhang, Xuanfeng; Yan, Song; QuanQi,
Abstract : It is very important to study and explore the application of virtual reality technology in landscape garden design, especially in the current environment of triple network integration and Internet of Things construction, to promote and facilitate the rapid development of digital landscape garden design in China. In this paper, we study the implementation method of virtual landscape gardening system and establish a virtual environment based on the ancient city of Yangcheng. On the computer platform, we study and realize a virtual roaming system of medium complexity with more complete roaming functions. Using the Quest3D software platform, a desktop-type virtual garden simulation system was developed, focusing on the virtual reality modeling technology method and virtual system implementation. The experimental results show that the GPU-accelerated drawing method based on GLSL can significantly improve the drawing frame rate of 3D garden landscape vegetation scenes with a small amount of scene data and has a certain feasibility. Based on the OpenSceneGraph (OSG) graphics rendering engine, the visualization of various types of 3D landscape models is realized, and the spatial layout of various types of landscape with parametric control is realized through digital vector layers, which flexibly manage and organize various garden elements and reasonably organize the spatial topological relationship between various types of landscape in 3D space. By integrating cross-platform ArcGISEngine components, the basic data of garden scenes including terrain data and vector data are managed. Through scene view cropping and hierarchical detail modeling technologies, the drawing efficiency and rendering real time of the garden landscape are improved. It realizes interactive 3D scene browsing and provides a six-degree-of-freedom all-round display of the overall landscape.